2018
DOI: 10.1097/j.pain.0000000000001232
|View full text |Cite
|
Sign up to set email alerts
|

Altered prefrontal correlates of monetary anticipation and outcome in chronic pain

Abstract: Chronic pain may alter both affect- and value-related behaviors, which represents a potentially treatable aspect of chronic pain experience. Current understanding of how chronic pain influences the function of brain reward systems, however, is limited. Using a monetary incentive delay task and functional magnetic resonance imaging (fMRI), we measured neural correlates of reward anticipation and outcomes in female participants with the chronic pain condition of fibromyalgia (N = 17) and age-matched, pain-free, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
130
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(168 citation statements)
references
References 89 publications
30
130
8
Order By: Relevance
“…It remains unclear however, whether the neural activation during reward consumption in migraine could be similar to the brain response found in different chronic pain syndromes. A recent study for example, detected different BOLD-responses to reward consumption between fibromyalgia (FM) patients and controls 33 . The authors found increased mPFC activity yielded for no loss outcomes compared to controls, which could indicate that FM patients tend to process no loss outcomes as a reward or relief rather than just a “zero sum” situation like healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains unclear however, whether the neural activation during reward consumption in migraine could be similar to the brain response found in different chronic pain syndromes. A recent study for example, detected different BOLD-responses to reward consumption between fibromyalgia (FM) patients and controls 33 . The authors found increased mPFC activity yielded for no loss outcomes compared to controls, which could indicate that FM patients tend to process no loss outcomes as a reward or relief rather than just a “zero sum” situation like healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, beyond the nature of rewards, it is worthwhile to investigate separately the neural responses during different stages of reward processing 32 . Although our understanding of the secondary reward anticipation and consumption in migraine is very limited, a recent study of fibromyalgia patients 33 found reduced medial prefrontal cortex (mPFC), ACC and VTA activity during gain anticipation, and heightened mPFC activity during non-punishment outcomes compared to controls. Based on these differences in corticostriatal processing during reward anticipation and consumption in chronic pain, we could hypothesize differences in migraine as well.…”
Section: Introductionmentioning
confidence: 99%
“…In sum, the studies by Gandhi et al (2013) and Martucci et al (2018) both suggest altered reward processing during pain.…”
Section: Effects Of Pain On Reward Processingmentioning
confidence: 86%
“…Taken together, Gandhi et al interpret these results as an increased motivation to obtain reward without accompanying increased pleasantness of the reward. On the other hand, a study comparing patients with the chronic pain condition fibromyalgia (n = 17) to a group of healthy controls (n = 15) found no difference in response times in the MID task (Martucci et al, 2018). Nevertheless, patients and controls differed in terms of brain activation during reward anticipation and outcome, measured using fMRI.…”
Section: Effects Of Pain On Reward Processingmentioning
confidence: 96%
See 1 more Smart Citation